Meningkatkan Kemampuan Motorik Halus Anak Melalui Permainan Paper Cup Pada Usia 4-5 Tahun Di TK Qurrota A’yun 01 Aisyiyah Kota Pekalongan Tahun Ajaran 2020/2021 - Rusdianah Rusdianah (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2022)
This study aims to improve the fine motor skills of children in QURROTA A'YUN 01 AISYIYAH KOTA PEKALONGAN at the age of 4-5 years. This study uses classroom action research (CAR). The research subjects at QURROTA A'YUN 01 AISYIYAH TK, PEKALONGAN CITY, group A consisted of 16 children, 8 boys and 8 girls. Data collection techniques through observation and documentation. The results showed an increase in children's fine motor skills through the use of the